2018
DOI: 10.1088/1361-6528/aaa647
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficiency of hybrid amorphous silicon solar cells based on single-walled carbon nanotubes and polymer composite thin film

Abstract: We report a simple approach to fabricate hybrid solar cells (HSCs) based on a single-walled carbon nanotube (SWCNT) film and a thin film hydrogenated amorphous silicon (a-Si:H). Randomly oriented high quality SWCNTs with an enhanced conductivity by means of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate are used as a window layer and a front electrode. A series of HSCs are fabricated in ambient conditions with different SWCNT film thicknesses. The polymethylmethacrylate layer drop-casted on fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In hybrid crystalline silicon (c-Si) solar cells, PEDOT:PSS has been demonstrated to be a very efficient electron blocker, acting as “ideal” barrier [9,10,11] or passivation material [12] in heterojunction intrinsic thin film (HIT) solar cells, acting as a substitute of p-type material. PEDOT:PSS thin films have also shown potential to be used with amorphous silicon as a p-type window layer in PV devices [13,14,15] due to their large bandgap (~1.6 eV) and high work function (~5 eV). Moreover, the p-type polymer layer has the potential to simplify the fabrication of the frontal interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In hybrid crystalline silicon (c-Si) solar cells, PEDOT:PSS has been demonstrated to be a very efficient electron blocker, acting as “ideal” barrier [9,10,11] or passivation material [12] in heterojunction intrinsic thin film (HIT) solar cells, acting as a substitute of p-type material. PEDOT:PSS thin films have also shown potential to be used with amorphous silicon as a p-type window layer in PV devices [13,14,15] due to their large bandgap (~1.6 eV) and high work function (~5 eV). Moreover, the p-type polymer layer has the potential to simplify the fabrication of the frontal interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Single-walled carbon nanotube (SWCNT) films have been proven to be prospective candidates for numerous applications in many fields of science and technology. Among the most promising examples of SWCNT implementations are transparent electrodes, 1,2 smart textiles, 3,4 ultrasensitive photodetectors, 5,6 highly-efficient solar cells, 7,8 light-emitting diodes, 9,10 and ultrafast lasers for near and midinfrared wavelength ranges. 11,12 All these applications, as well as almost any task related to the development of devices based on SWCNT films, strongly require a rapid, versatile, and preferably contactless method to determine the film thicknesses and their optical properties.…”
mentioning
confidence: 99%
“…For more details on the pin‐diode theory, the reader is suggested to review relevant literatures (Schropp & Zeman, 1998; Shah, 2010; Street, 1991). During the last decade, the use of carbon nanotubes in thin film amorphous silicon has been of great interest for researchers as light trapping structures, antireflective coatings, transparent electrodes, and p‐type window layer contacting a‐Si:H to form heterojunction (Alekseeva et al, 2018; Del Gobbo et al, 2011; Funde et al, 2016; J. Kim et al, 2012; P. M. Rajanna et al, 2018, 2019; Schriver et al, 2010; Tu et al, 2012; Zhou et al, 2014, 2008, 2009). Similar to SWCNTs/c‐Si heterojunction (Hu et al, 2019; Jeon et al, 2018; Tune et al, 2012), SWCNTs/a‐Si:H also form semiconductor/semiconductor or metal/semiconductor junction as shown in Figure 1a,b.…”
Section: Swcnts/a‐si:h Heterojunction Solar Cellsmentioning
confidence: 99%
“…Several reviews exist that highlights the progress made in SWCNT/c‐Si solar cells (Hu et al, 2019; Jeon et al, 2018; Jia et al, 2008; Xinming Li et al, 2015; Tune et al, 2012, 2020; Tune & Flavel, 2018). Also, heterojunction solar cells combining a‐Si:H and SWCNTs thin film have been reported that have progressed from around 0.03% to 8.80% during the same time (Alekseeva et al, 2018; Del Gobbo et al, 2011; Funde et al, 2016; P. M. Rajanna et al, 2018, 2019; Schriver et al, 2010). The focus on using SWCNT thin films in a‐Si:H is to prevent the use of any standard p‐(boron or aluminum) doped a‐Si:H or microcrystalline silicon, ITO and other traditional metal layers like Au, Ag, Al, and Cu.…”
Section: Introductionmentioning
confidence: 99%